Reel inequality : Hollywood actors and racism - Yuen, Nancy Wang, 1976- (Rutgers University Press, 2017)
Not only are #OscarsSoWhite, but white male gatekeepers dominate Hollywood, breeding a culture of ethnocentric storytelling and casting. Reel Inequality examines the structural barriers actors of color face in Hollywood, while shedding light on how they survive in a racist industry. Through nearly a hundred interviews with working actors, Nancy Wang Yuen reveals the biases they experience in talent agents' offices, at auditions, and on sets, yet also provides vital insights from actors of color who have succeeded on their own terms.